Assessment of Computed Tomography Dose Index (CTDI) During CT Pelvimetry Using Monte Carlo Simulation - M. Aabid; S Semghouli; A. Choukri (National Research and Innovation Agency, 2023)
A pelvimetry examination is sometimes prescribed to a pregnant woman at the end of her pregnancy in order to assess the dimensions of her pelvis prior to childbirth. This examination has long been performed by using X-ray, but is now increasingly being replaced by CT-scan The objective of this study is to assess the radiation doses received during a practical CT pelvimetry examination performed using a Hitashi Supria 16-slice CT scanner. The radiation doses were estimated using Monte Carlo (MC)-based simulation with GATE code to model the 16-slice CT scanner machine. The GATE code operates using GEANT4 libraries. A polyymethyl metacrylate (PMMA) acrylic phantom of 32 cm diameter was modeled to represent the patient's body. X-ray energy spectrum generated using the SRS-78 spectrum processor was used for simulation. The simulation was executed with the same exposure parameters as the practical CT pelvimetry examination with dose parameters of 1 mGy, 0.9 mGy, and 36.6 mGy.cm, respectively, for the weighted CT dose index (CTDIw), the volume CT dose index (CTDIvol), and dose-length product (DLP). The MC simulation results provide dose parameters of 1.16 mGy, 1.07 mGy, and 43.6 mGy.cm, respectively, for the CTDIw, CTDIvol, and DLP. The differences between the simulation and the practical examination were 16 %, 18 %, and 18 %, respectively. These differences are considered in a quite good agreement. The results were also consistent with other similar studies. This work proves that the Monte Carlo simulation with the GATE code is usable to assess the patient doses during a CT pelvimetry examination.